The effects of worked examples presentation on sub-cognitive loads - Yusof, Yusniza; Lai, Chee Sern; Lee, Ming Foong (American Scientific Publishers, 2017)
One promising technique for helping students in fulfilling complex problem solving tasks is through learning with worked example. Although worked example approach is the most prominent technique discussed in the literature of cognitive load theory, there is still very little scientific understanding of managing the students’ sub-cognitive load, namely intrinsic, extraneous and germane load on different complexity of worked example approach especially in engineering domain. Thus, this study was conducted to investigate the effects worked examples presentation on sub-cognitive loads among electrical engineering students. In this research, the worked examples were presented in three different sequences: (i) all examples were of same level of difficulty (ii) from difficult to easy example; (iii) from easy to difficult example. Data were collected from 82 students (Condition (i) =27; Condition (ii) = 34; condition (iii) = 21) of Diploma in Electrical Engineering Program at three selected polytechnics. The inventory tool of sub cognitive load were given to students after each teaching and learning session ends. The findings suggested that worked examples presented in easy to difficult format could be one of the approaches that is more efficient to manage students’ cognitive load and effective to be applied in engineering lessons